PEMBERDAYAAN PEREMPUAN PELAKU USAHA KECIL MELALUI INOVASI PRODUK OLAHAN BUAH PALA DI DESA WANAYASA KECAMATAN WANAYASA KABUPATEN PURWAKARTA - Huraerah, Abu; W, R Willya Achmad (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
This empowerment activity aims to: (a) make maximum use of nutmeg as an agricultural commodity; (b) empowering the Wanayasa Village community in the production of processed nutmeg; (c) increasing the income of small business actors through diversifying processed nutmeg products, namely syrup, jelly candy and sheet jam; (d) develop business activities for processed nutmeg products by involving business actors, such as: traders, stall owners, outlets and distributors; and (e) building networks between stakeholders and partnerships with business actors, village communities, BUMDes/Badan Usaha Milik Desa (Village-Owned Enterprises), Cooperatives, Universities (Universitas Pasundan), Cooperative Services and UMKM/Usaha Mikro, Kecil, dan Menengah (MSME/Micro, Small and Medium Enterprises), Purwakarta Regency Industry and Trade Service, and Banking. Increased knowledge and understanding of MSME actors and pioneers in simple bookkeeping and marketing strategies for processed nutmeg MSMEs. The activity implementation methods used are (a) Training method; (b) technical guidance methods; and (c) facilitation approach method. The results of community empowerment activities are (a) increasing the skills of MSME actors and pioneers in practicing diversification of processed nutmeg production (syrup, jelly candy, sheet jam); (b) MSME actors are not yet skilled in packaging processed nutmeg products that can attract buyers; (c) no application has been made to obtain a simple patent for processed nutmeg products from the Ministry of Law and Human Rights; and (d) there has not been a test on the expiry/validity period of processed nutmeg products and a test on the content/content of processed nutmeg products.